Complete Heart Block Secondary To Leptospirosis: A Case Report - Mohammad Isa, Muhammad Syafiq bin; Wan Ali, Wan Ahmad Syahril Rozli (Jurnal Ilmu Kesehatan dan Kesehatan, 2024)
Complete heart block (CHB) is a rare but potentially life-threatening complication of leptospirosis, a zoonotic bacterial infection caused by spirochetes of the genus Leptospira. While leptospirosis primarily affects the kidneys and liver, cardiac involvement, including CHB, can occur and has significant clinical implications. The pathogenesis of CHB in leptospirosis is multifactorial and may involve direct cardiac invasion by Leptospira organisms, systemic inflammatory response, autoimmune reactions, electrolyte imbalances, and hemodynamic effects. Prompt recognition and management of CHB are essential to prevent adverse outcomes, including hemodynamic instability and sudden cardiac death. Treatment strategies include supportive measures such as hemodynamic support and correction of electrolyte imbalances, temporary pacing for symptomatic bradycardia, antibiotic therapy for the underlying infection, and consideration of permanent pacemaker implantation in refractory cases. Cardiac manifestations may include myocarditis, pericarditis, arrhythmias, conduction blocks and cardiac failure. We are reporting a case of leptospirosis causing complete heart block in a previously healthy young gentleman.